Experiences and quality of life of the elderly during the Covid19 pandemic and the introduction of restrictive measures in Serbia - Dzamonja Ignjatovic, Tamara Z; Stanković, Biljana; Klikovac, Tamara (Psihološka istraživanja, 2020)
This paper is part of a broader qualitative study examining the experience of people during the first wave of the pandemic in Serbia when the state of emergency was introduced, and the effects of this situation on the quality of life and mental health of specific age groups. The paper presents the results of interviews conducted with people over 65, who were particularly affected by the introduced restrictive measures, due to which many senior citizens felt a significant decline in quality of life, accompanied by the risk of developing various emotional problems. In order to understand better their specific experiences during the pandemic and related measures introduced, we conducted the qualitative study taking into account the characteristics of previous life contexts, changes in daily life and life quality during the pandemic, emotional reactions and coping strategies, as well as their expectations of the future.There were interviewed 16 people, both sexes (4 men), age 65 to 87 years (M = 71.19 years), during April and early May 2020. Transcripts of semi-structured interviews were processed in Maxqda qualitative analysis software and analyzed by the principle of thematic analysis.The general conclusion is that the elderly from our sample adapted without major difficulties and managed to maintain satisfaction of the subjective well-being despite the pandemic and restrictive measures, and with the help and support of the social environment in the context of the former general quality of life. This resulted in good adaptive strategies and outcomes, beside restricted  need satisfaction. However, the findings of the research indicate that the reactions to the pandemic in the elderly differ from the reactions to the introduced measures - the tolerance of the elderly to the endangerment of personal needs is greater than the tolerance to the endangerment of personal rights and dignity. While the concern about one's own health was not explicitly expressed, the citizens older than 65 felt more affected by the introduction of a state of emergency and especially restrictive measures. Measures of isolation were reflected in increased negative feelings and a decline in the quality of life, but also in the threat to personal dignity.
Keywords: Pandemic Covid19, the elderly, quality of life, subjective wellbeing, coping strategies